Affirmation as a Method of Implementing Islamic Values in Social and Science Learning - Saipul Umar; Agung Gumelar (EDUPEDIA Publisher, 2023)
Affirmations are psychologically very powerful in influencing positive changes to one's personality. One of the affirmation techniques is to use positive sentences, in the form of Islamic values built from science and social science learning materials. This research uses a mixed method (Mixed Methode Research) taking a population of grade 2 students at Madrasah Aliyah Darul Huda in OKU Selatan District. The analysis was carried out by interpretive and inferential statistical analysis. The results of the study prove that integrating principles in each sub-subject of science and social studies with Islamic values, conveyed by an affirmative approach is able to shape Islamic behavior in MA students. It can be concluded that affirmation as a teaching and learning process, which absorbs Islamic values that are integrated from each science learning sub-material has been shown by students in social behavior and behavior of order, balance, beauty and cause and effect. Students are also able to demonstrate behavior which is the absorption of social science with Islamic values such as compassion, togetherness, honesty and generosity.